2015
DOI: 10.1515/secm-2013-0274
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of tensile and bending properties of biaxial weft knitted composites

Abstract: Within the scope of experiments, the effect of aramid and glass yarns as stitch and biaxial (warp and weft) yarns in the biaxial weft knitted (BWK) composite was compared. After production of four types of composite panel using the hand lay-up method, the tensile and bending properties of the BWK composites were investigated both experimentally and numerically. The composite with the glass stitch and biaxial yarns exhibited higher tensile and bending properties than did the composite with the aramid stitch and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…reported that the tensile properties of BWK reinforced composites could be successfully estimated with finite element modelling. 26 Hessami et al. 21 examined tensile and flexural behaviour of the BWK reinforced composites using experimental and finite element modelling methods.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the tensile properties of BWK reinforced composites could be successfully estimated with finite element modelling. 26 Hessami et al. 21 examined tensile and flexural behaviour of the BWK reinforced composites using experimental and finite element modelling methods.…”
Section: Introductionmentioning
confidence: 99%
“…In order to simplify the investigation of textile structures, lots of methods including the analytical method (used for meso-mechanical parameters) and numerical method (mostly known as the finite element method) are available. The good agreement between the experimental and analytical results of the composites tensile and bending properties found by Demircan et al is considered as the high ability of finite element method for simulating the mechanical behavior of biaxial weft-knitted composites [123].…”
Section: Modeling the Mechanical Properties Of Bwkfsmentioning
confidence: 65%
“…Besides the experimental investigations, Demircan et al developed a theoretical model in order to investigate the mechanical performance of biaxial weft-knitted composites [3,123]. In general, textile fabrics with periodic structures are difficult to be investigated in terms of elastic properties of a unit cell.…”
Section: Modeling the Mechanical Properties Of Bwkfsmentioning
confidence: 99%
“…A simulation approach would reduce the developing time and cost. Therefore, many models for various textile structures such as woven fabrics [9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], 3D woven fabrics [30,31,32,33,34,35,36], non-crimp fabrics [37], weft-knitted fabrics [17,38,39,40,41,42,43,44,45,46,47], and multiaxial warp-knitted fabrics [48] were developed. The models could be classified by the mathematical approach: Analytical [44,49,50] or numerical models, in which they are divided into smaller groups by the length scale of the modelled components into three categories: Micro-scale models [20,21,35,36,39], meso-scale models [16,17,18,19,22,31,32,33,34,37,40,41,42,…”
Section: Introductionmentioning
confidence: 99%
“…A composite unit cell with 3D tetrahedral elements coupled with a matrix mesh helps to predict the mechanical behavior of the weft-knitted reinforced composite. Similar approaches using a meso-scale model on a repeated unit cell are also used for numerical analysis of the mechanical behavior of the weft-knitted structure [40,42,46] or weft-knitted reinforced composite structure [38,47,53,54]. The obtained properties can be transferred to macro-scale model for further analysis.…”
Section: Introductionmentioning
confidence: 99%